Neuroprotective effect of the 3α5β-pregnanolone glutamate treatment in the model of focal cerebral ischemia in immature rats - Kleteckova, Lenka; Tsenov, Grygoriy; Kubova, Hana; Stuchlik, Ales; Vales, Karel (Neuroscience letters, 2014)
The perinatal hypoxic-ischemic insult frequently leads to mortality, morbidity and plays a key role in the later pathological consequences. The ischemic insult causes a massive release of glutamate and subsequent excitotoxic damage. The neuroactive steroid 3α5β-pregnanolone glutamate (PG) is a NMDA receptor antagonist acting via use-dependent mechanism and can be used as a neuroprotective agent that may alleviate glutamatergic excitotoxicity in the brain. First, a possible neurotoxic effect of the PG, a novel use-dependent NMDA antagonist, was studied in immature rats. In addition, to compare this effect with a well-described non-competitive NMDA antagonist, the MK-801 (positive control) was used. Animals at postnatal day 12 (P12) were injected intraperitoneally with PG in a doses 1 or 10mg/kg or with MK-801 in a dose 1mg/kg. Effect of PG treatment on the immature brain was evaluated on Fluoro Jade B (FJB) stained sections. Second, a neuroprotective effect of the PG was studied in the model of focal cerebral ischemia in P12. Focal cerebral ischemia was induced by the infusion of the endothelin-1 (ET-1) into the right dorsal hippocampus. PG at the doses 1 or 10mg/kg was administrated intraperitoneally 5min after the end of ET-1 infusion. To evaluate the neuroprotective effect after the PG treatment FJB staining was used. Our results demonstrate a lack of the neurotoxicity of the PG in intact P12. In the second part of the study in the model of the focal ischemia we detected significantly lower occurrence of FJB-positive cells in the afflicted hippocampus in PG treated groups, while animals without PG treatment exhibited massive neurodegeneration. The neuroprotective potential of the PG can serve in the development of therapeutic strategies for brain damage induced by the glutamate excitotoxicity.
Keywords: NMDA receptors; Brain Ischemia; Pregnanolone; Neuroprotective Agents; krysa rodu Rattus; Hippocampus; potkani Wistar; receptory N-methyl-D-aspartátu; ischemie mozku; Disease Models, Animal; Rats, Wistar; neuroprotektivní látky; glutamáty; mužské pohlaví; Endothelin-1; 3α5β-Pregnanolone glutamate; pregnanolon; zvířata; Focal cerebral ischemia; Glutamates; Rats; Receptors, N-Methyl-D-Aspartate; Animals; Male; hipokampus; Immature rats; modely nemocí na zvířatech